Dementia as a risk factor for 30-day mortality in community-acquired pneumonia in Colombia (CAP): A survival study - Juan Sebastian Hernández-Puentes; Alirio Rodrigo Bastidas-Goyes; Eduardo Tuta-Quintero; Diana Díaz-Quijano; Nicole Méndez Peñalosa; Nayah Zuleta Sanchez; María Herran Perez; Juan Rodríguez Sánchez; Valentina Ortiz Marquez; Ana Colmenares Leal; Juanita Zuleta Montañez; Laura Riveros Pedraza; et al. (PLoS ONE, 2025)
Background Community-acquired pneumonia (CAP) represents a significant clinical challenge, particularly in patients with comorbidities, such as dementia, which increases the risk of mortality and hospitalization. Despite its relevance, dementia has not been considered a CAP severity assessment tool. Furthermore, there is limited information on this topic in Latin America. Therefore, this study aimed to analyze 30-day survival in patients with CAP and dementia in Colombia with the objective of identifying the impact of dementia on clinical outcomes and understanding this phenomenon in the region. Methods A multicenter retrospective cohort study with survival analysis was conducted on patients with CAP admitted to two tertiary care institutions in Colombia between January 2010 and December 2020. Results The study included 3,374 subjects: 354 (10.5%) with dementia and 3,020 (89.5%) without dementia. The mean age was 65.5 years, higher in the dementia group (82.5 vs. 63.5 years, p < 0.001). Patients with dementia showed a higher prevalence of cyanosis, retraction, altered consciousness, and rales (p < 0.001). They also had higher rates of hypertension, heart failure, cerebrovascular disease, and chronic kidney disease (p < 0.001). Laboratory findings showed lower hemoglobin and sodium levels and higher BUN levels (p < 0.001). The 30-day mortality was 26.3% in the dementia group and 7.1% in the non-dementia group (p < 0.001), with a HR of 2.28 (95% CI: 1.756–2.962). The 30-day survival rate was 73.7% and 92.9%, respectively (p < 0.001). Conclusion Patients with dementia who developed pneumonia had a significantly higher mortality rate. They were also characterized by advanced age, multiple comorbidities, and greater disease severity. Our findings emphasize the importance of prioritizing individualized care to improve clinical outcomes and quality of life.